PANDANGAN FIKIH TERHADAP TRADISI NGEJOT DAN MEGIBUNG UMAT MUSLIM DAN HINDU DI BALI - Liyana Rakhmawati (Institut Agama Islam Hasanuddin Pare, 2024)
This paper aims to examine the interaction of tolerance between Muslims and Hindus in Bali through the Ngejot and Megibung traditions with a fiqh perspective. This tradition can be found in Muslim villages in Bali. Such as the Kepaon Islamic village, Denpasar City, Gelgel Islamic Village, Klungkung Regency, Saren Jawa Islamic Village, Karangasem Regency and other Muslim villages. For some Muslims, there are still those who reject this tradition carried out by Muslims. Because these two traditions are traditions of the Hindu community in Bali. The method and type of this research is library research by collecting books, journals, and research results that support the research theme, namely literature on the Ngejot tradition, Megibung and other practices of tolerance interaction in Bali which are then studied with Islamic law (fiqh). In fiqh literature, the tradition termed as ‘ada is divided into two kinds. First, the fasid tradition, which is a tradition that is inconsistent with and contrary to the provisions of Islamic law. Second, authentic traditions, namely traditions that are in harmony and do not conflict with the provisions of Islamic law. The Ngejot and Megibung traditions in the view of fiqh are authentic traditions.